2011
DOI: 10.1007/bf03262776
|View full text |Cite
|
Sign up to set email alerts
|

Molar Incisor Hypomineralisation: prevalence in Jordanian children and clinical characteristics

Abstract: MIH was common among 7-9 year-old Jordanian children with a prevalence of 17.6% and was gender related. MH was more common than MIH and can be considered a mild form of an MIH spectrum. Majority of MIH and MH cases were mild in nature but demonstrated an agerelated severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
48
7
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 21 publications
16
48
7
4
Order By: Relevance
“…It is noteworthy to mention that Elfrink and colleagues stated that to conduct an MIH prevalence study a minimum random sample size of 300 is required 20 . Upon completing a literature review in regards MIH, a total of three other research carried out in Arab settings were identified, with the countries of context Iraq 23 , Jordan 24 and Libya 25 . These studies highlighted prevalence rates of 21.5%, 17.6% and 2.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to mention that Elfrink and colleagues stated that to conduct an MIH prevalence study a minimum random sample size of 300 is required 20 . Upon completing a literature review in regards MIH, a total of three other research carried out in Arab settings were identified, with the countries of context Iraq 23 , Jordan 24 and Libya 25 . These studies highlighted prevalence rates of 21.5%, 17.6% and 2.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PFMs hypo-mineralization was similarly distributed between quadrants and arches which was consistent with some previous studies (Weerheijm et . Some of those researchers attributed the high prevalence in mandibular molars to the fact that differences in examination conditions may make it hard to view maxillary molars as clearly as mandibular molars (Mittal et al, 2016), and the early eruption with early posteruptive enamel breakdown or caries makes the mandibular more prone than maxillary molars (Zawaideh et al, 2011). On the other hand, Chawla et al, (2008) explained the higher prevalence of hypo-mineralization in the maxillary PFMs by the same reasons analyzed differently.…”
Section: Discussion:-mentioning
confidence: 99%
“…There was no significant difference with regards to gender. Mittal have shown that the prevalence rate in India is 6.31% [8], 2.8% in Hong Kong Cho [9], 17.6% in Jordan Zawaideh [10], 18.6% in Iraq [11], and 4% to 25% in Europe [3,4]. Regional differences might be correlated with the environment of child's growth and development, diagnostic criteria, statistical methods, and age.…”
Section: Discussionmentioning
confidence: 99%